Ganti Kerugian Berdasarkan Perjanjian Antara Pengembang Perumahan dengan Konsumen di Atas Tanah Rawan Banjir - Supeno Supeno (Wajah Hukum, 2020)
The purpose of this study is to give critical thinking to the housing developers who build housing in a flood area that impacts the consumer. The study is based on the incidence of residential land that has flooded in the rainy season, the study was peeled with the prevailing regulatory approach. Results show that the developer's obligation has not been included to compensate the consumer in agreement between the developer and the consumer in case of flooding in residential prone to flood so consumers suffer losses, it is not a state of force (force majeur) because to be said in a state of forced (force majeur) must fulfill the elements of article 1244 Civil Code. To provide the protection of the law for consumers, from the beginning of the agreement must be stated that the housing purchased by consumers is in a safe location of flooding, so that if there is a flood of consumers have a strong legal basis to demand developers. Residential developers must have good faith to carry out the agreements that have been made including compensation in the event of a flood.